2013
DOI: 10.5103/kjsb.2013.23.2.091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Warm-up Procedures on Bat Speed in Baseball

Abstract: The purpose of this study was to compare the effect of a new warm-up condition, overloaded arm weights (721 g each arm,[OA]), on the bat speed during warm-up and immediately after warm-up with traditional warm-up conditions such as no-extra mass warm-up (control condition, [CO]) and overloaded bat warm-up (885 g donut on a bat, [OB]) conditions. Twenty male subjects who had competitive baseball experience participated in this study. Electromagnetic motion capture system was used to capture body segment motions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…This implies that maximal performance does not occur immediately following the training stimulus, thus explaining the delayed enhancement of performance following a weighted implement protocol as exhibited in the study of Wilson et al (53). This model may also explain the findings of other included studies who experienced similar delayed performance enhancements (21,50). Wilson et al (53) also referred to the possible elicitation of postactivation potentiation (PAP) following the use of overweighted bats as a potential mechanism for subsequent performance.…”
Section: Discussionmentioning
confidence: 86%
“…This implies that maximal performance does not occur immediately following the training stimulus, thus explaining the delayed enhancement of performance following a weighted implement protocol as exhibited in the study of Wilson et al (53). This model may also explain the findings of other included studies who experienced similar delayed performance enhancements (21,50). Wilson et al (53) also referred to the possible elicitation of postactivation potentiation (PAP) following the use of overweighted bats as a potential mechanism for subsequent performance.…”
Section: Discussionmentioning
confidence: 86%
“…In conclusion, research has shown multiple techniques may be used to increase bat velocity using both ondeck/short-term and training/long-term strategies. When using on-deck warm-up implements for increasing bat velocity, sport coaches as well as strength and conditioning coaches should encourage players to utilize implements that are within ± 12% of the standard bat weight, according to previous research (Kim, 2013;Szymanski et al, 2011;Szymanski et al, 2012;Wilson et al, 2012). Training, or long-term, strategies should emphasize similar weights to the on-deck strategies and rely heavily on periodization to increase the likelihood of success.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this theory, multiple studies have tested the effect of warm-up devices on bat velocity. Surprisingly, the majority of the studies showed that there was no difference in bat velocity or that warming up with heavier weighted implements (>12% standard bat weight) showed a reduction of bat velocity (Kim, 2013;Szymanski et al, 2011;Szymanski et al, 2012;Wilson et al, 2012). In spite of no beneficial change in bat speed, coaches and athletes may gravitate toward heavier implements because of the sensation of greater "normal" bat speed, identified as "kinesthetic aftereffect" (Southard & Groomer, 2003).…”
Section: On-deck / Short-term Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in the four records with EM tag in Table 2, each sensor is able to read location and orientation simultaneously, but any metal object in the vicinity of sensors may introduce distortions in the magnetic field, ruining measurement accuracy. For example, in (Y.-K. Kim, 2013), the weighting supplement on arms and bats (Valeo, USA), as well as the bat itself, is non-metal to avoid interferences with the 4" by 4" global reference frame transmitter. Only two manufacturers are used in these records: on the one hand, Polhemus, USA, in a single-sensor setup, ranging from 60 Hz (Kasmer, Ketchum, & Liu, 2014) to 120 Hz (Norcross et al, 2013a(Norcross et al, , 2013b and on the other hand, Motion Star, USA, in a 12-sensor setup working at 240 frames per second.…”
Section: Non-optical Systemsmentioning
confidence: 99%